Analysis of the Effect of Traffic Volume on Road Service Level Based on PM KM 14 Year 2024 - Muhammad Chaiddir Hajia; La Sianto (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
Wolter Monginsidi Street is one of the main activity hubs in Baubau City. It serves as a central shopping area, making it prone to traffic congestion due to the increasing traffic volume caused by human movement and transportation activities. This road stretches 600 meters and is lined on both sides with textile shops, clothing stores, and grocery shops. It also frequently accommodates vehicles coming from the direction of Pasar Karya Nugra, further escalating the traffic volume. The problem examined in this study is the impact of traffic volume on the service level of Wolter Monginsidi Street, assessed based on Regulation PM No. 14 of 2006. The study aims to determine the influence of traffic volume on the road's service level following the latest regulations outlined in PM No. 14 of 2006. Based on the analysis, the following conclusions were drawn: The traffic performance on Wolter Monginsidi Street is categorized as good since the road's capacity is sufficient to handle peak-hour traffic volumes. The service level of Wolter Monginsidi Street is classified under Service Level Category B